2021
DOI: 10.3389/fmicb.2021.772420
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbiome: The Emerging Barrier in Plant-Pathogen Interactions

Abstract: In the ecosystem, microbiome widely exists in soil, animals, and plants. With the rapid development of computational biology, sequencing technology and omics analysis, the important role of soil beneficial microbial community is being revealed. In this review, we mainly summarized the roles of rhizosphere microbiome, revealing its complex and pervasive nature contributing to the largely invisible interaction with plants. The manipulated beneficial microorganisms function as an indirect layer of the plant immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 76 publications
1
44
0
1
Order By: Relevance
“…(Kwak et al 2018). It is well established that plants become enriched for beneficial microbes when challenged by fungal pathogens (reviewed in (Bakker et al 2018;Li et al 2021). In the 14 frame of "Cry-for-Help" hypothesis, several studies have shown the potential of plants to recruit beneficial microbes from the untapped soil reservoir (Bakker et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…(Kwak et al 2018). It is well established that plants become enriched for beneficial microbes when challenged by fungal pathogens (reviewed in (Bakker et al 2018;Li et al 2021). In the 14 frame of "Cry-for-Help" hypothesis, several studies have shown the potential of plants to recruit beneficial microbes from the untapped soil reservoir (Bakker et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It must be acknowledged that plant immunity is a function of innate immunity mechanisms against incoming pathogens, as well as, microbiota-mediated disease resistance [ 186 , 187 ]. Effectors are important determinants which shape microbial communities, determining their lifestyle, level of host specialization as well as their compatibility with other microorganisms [ 188 ].…”
Section: Effectors and Plant Defensementioning
confidence: 99%
“…Rhizospheric microbes are the significant players in nutrient cycling that play an essential role in plant development ( Bulgarelli et al, 2013 ; Francioli et al, 2016 ; Müller et al, 2016 ). The plant rhizosphere contains beneficial and pathogenic microbes competing for nutrients and space ( Raaijmakers et al, 2009 ; Adesemoye et al, 2009 ; Beans, 2017 ; Li et al, 2021 ). Tomato root rot caused by sclerotia forming fungus Rhizoctonia solani , is a highly destructive disease that severely affects crop development and yield ( Patil and Solanki, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…Most bacterial antagonists create an obliging interaction with plant roots that can modulate by the selective pressure of changing environment ( Bais et al, 2006 ; Falardeau et al, 2013 ). For example, it is well known that pathogens influence the production and diffusion of root exudates ( Guo et al, 2015 ; Hoysted et al, 2018 ; Pascale et al, 2020a ; Li et al, 2021 ). Interestingly, plant-pathogen associations are modulated through native microbial communities during infestation and resistance ( Chiu et al, 2017 ; Stevens et al, 2021 ; Dubey et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%